ANALISIS KETEPATAN WAKTU PENYAMPAIAN LAPORANKEUANGANKEPADAPUBLIK: STUDI EMPIRIS PADA PERUSAHAAN MANUFAKTUR YANG TERDAFTAR DI BEI - Fauziah Aida Fitri; Nazira Nazira (Program Magister Akuntansi Unsyiah, 2009)
Demands for compliance with timely submission of financial reports to the public in Indonesia has been stipulated in the Law N0.8 Year 1995 concerning Capital Market and Bapepam Decision No.80/PM/1996 on financial reporting obligations periodiccally. Process in achieving timely financial statement presentation to the public becomes increasingly difficult because of the increasing growth of existing public companies in Indonesia.This study aims to examine empirically the effect of firm size, liquidity, company age, and reporting of exceptional items and / or contingent on timely submission of financial reports on companies listed on Indoneia Stock Exchange (BEI). The selection of samples to be used in this study was purposive sampling. Samples are manufacturing companies listed on the Stock Exchange with the following criteria: a) the company issued financial statements as of December 31 for the years 2004 to 2007; b) the company whose shares are actively traded in IDX. The data used is a form of secondary data obtained from annual reports and the Capital Market Reference Center. Then the data were analyzed using multiple regression.The research proves that company size has a significant impact on the timeliness of financial reporting. While life companies, liquidity, and extraordinary items and / or contingencies do not have a significant impact on the timeliness of financial reporting. Keywords: Timeliness, Financial Statements, Age, Size, Liquidity, xtraordinary items, Contingencies.